If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(6x + 4) = 238 Reorder the terms: 7(4 + 6x) = 238 (4 * 7 + 6x * 7) = 238 (28 + 42x) = 238 Solving 28 + 42x = 238 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-28' to each side of the equation. 28 + -28 + 42x = 238 + -28 Combine like terms: 28 + -28 = 0 0 + 42x = 238 + -28 42x = 238 + -28 Combine like terms: 238 + -28 = 210 42x = 210 Divide each side by '42'. x = 5 Simplifying x = 5
| y+3y-4=0 | | 8n=7+(n-1)(4) | | 4x+10+x=180 | | 3(2x+6)=84 | | 6=2x-5x^2 | | 4x+5=14+3x | | 150+16x=100+16x | | 4x^2+y^2+8x-4y-12=0 | | Y=60-14-10+2X | | x=8-2x^2 | | 2x+2=4x+8 | | 4/5x-2/3y=5/8 | | -4+-3y+4=3 | | 2.5(5r+1)+3.4r= | | 0.07(5t-9)=0.35(t+4)-2.03 | | 4x-0=-4 | | 5x+7=10+4x | | x^2+.713x-.13=0 | | (22b-2)-7(3b+1)=-6 | | 3x+4=4+6x | | -3x-15=-2x-2 | | 3(x-5)+7=6x-3(2+x) | | 7+7x=5x+27 | | f(x)=x^3-2x^2-3 | | 6x^5-24x^3=0 | | 6+6x+5x=72 | | (2x+11z)= | | -1.5+0.25=-4.2+-0.2 | | 3(3n+1)=7(7n+5)+5 | | 27r+(27r+2)=486 | | 57=5x+2x+1 | | 2/3n=5/12 |